Medication adherence of rheumatic heart disease patients: a cross-sectional study in Bangladesh - Wahab, Abrar; Islam, Md Mahabub Ul; Laboni, Mehbuba Mehnoor; Fatema, Anisa; Renesa, Abeda Saleha; Alam, Mohammad Morshad (Asian Journal of Medical and Biological Research, 2019)
Rheumatic heart disease (RHD) is a significant public health problem and Non-adherence to treatment is an important and often unrecognized risk factor for cardiovascular mortality. The study aimed to assess self-reported medication adherence by 8-item Morisky Medication Adherence Scale (MMAS-8) among rheumatic heart disease patients and determine the associated factors. A cross-sectional study was carried out by applying a structured interview to Rheumatic heart disease patients aged 18 or higher in a tertiary hospital in Bangladesh. Among Rheumatic heart disease patients, 63.5% showed medium adherence, 36.5% showed low adherence to medication. Walking habit (P= 0.000), exercise habit (P=0.000), smoking habit (P=0.000), and duration of RHD (P=0.005) found significantly associated with medication adherence. Multiple logistic regression analysis also revealed, don't have walking habit more than 10 minutes at a time (AOR=2.416, 95% CI: 1.212-4.816), don't having exercise habit (AOR=2.420, 95% CI: 1.206 – 4.859), don't having habit of smoking (AOR=0.392, 95% CI: 0.183 – 0.841), duration of RHD for less than 15 (AOR=4.190, 95% CI: 0.851 – 20.631) are independent predictors of adherence. Our study demonstrated medium to low medication adherence in the Morisky Medication Adherence Scale among rheumatic heart disease patients. Asian J. Med. Biol. Res. June 2019, 5(3): 186-191